Ethnoecology of the Gumesa Weaving Artisan Community in the Utilization of Natural Resources - Raden Dendy Anugrah; Inda Nur Cahyani; Fitri Sandya Arini (Yayasan Siti Widhatul Faeha, 2025)
Weaving ranks among the most ancient skills practiced by humans. A living example of this tradition can be found in Dusun Gumesa Timur, Desa Giri Tembesi, where the Tenun Dharmayasa group continues to preserve the art of weaving. The purpose of this study is to explore the history of the Dharmayasa weaving tradition, investigate the variety of plants utilized for natural dyeing purposes, identify the methods of sourcing raw materials, and understand the symbolic meanings behind the woven motifs. Through in-depth interviews, it was discovered that the Dharmayasa weaving group was formed because the local women possessed weaving skills that became essential for sustaining their livelihoods. In addition to synthetic dyes, they also use natural materials such as sappan wood, banana pseudostems, indigo plants, and gemitir (marigold) leaves to color the threads. A distinctive feature of Dharmayasa weaving is the